2015
DOI: 10.1093/ejcts/ezv239
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome and prognostic factors of surgically treated thymic carcinoma: results of 306 cases from a Japanese Nationwide Database Study

Abstract: R0 resection is essential for prolonged OS for surgically treated thymic carcinoma, but maximal debulking surgery might be beneficial and worth evaluating for advanced disease deemed difficult for R0 resection. The benefit of postoperative radiotherapy after R0 resection should also be evaluated prospectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 24 publications
3
102
1
2
Order By: Relevance
“…The optimal cut-off value for PD-L1 expression was defined on the basis of the ROC curve and Youden index (28,29). Here, Masaoka-Koga stage and surgical curability were taken into account as variables that significantly affect prognosis (8,30). Ultimately, either Masaoka-Koga stage I/IIa/IIb/III disease who all performed complete resection or stage IVa/IVb who undergone diagnostic biopsy was applied as a dichotomous variable, with PD-L1 expression as a continuous variable.…”
Section: Appraisal Of Pd-l1 Expressionmentioning
confidence: 99%
“…The optimal cut-off value for PD-L1 expression was defined on the basis of the ROC curve and Youden index (28,29). Here, Masaoka-Koga stage and surgical curability were taken into account as variables that significantly affect prognosis (8,30). Ultimately, either Masaoka-Koga stage I/IIa/IIb/III disease who all performed complete resection or stage IVa/IVb who undergone diagnostic biopsy was applied as a dichotomous variable, with PD-L1 expression as a continuous variable.…”
Section: Appraisal Of Pd-l1 Expressionmentioning
confidence: 99%
“…A previous report indicated that the incidence of nodal metastases in patients with thymic carcinoma was 26.8% (1). It has been confirmed by several studies that patients with thymic carcinoma receiving complete resection (R0) exhibit a more favorable long-term survival compared with those who undergo incomplete resection or do not receive surgery (1,5). …”
Section: Discussionmentioning
confidence: 93%
“…The majority of recurrences appear as pleural dissemination, mediastinal relapse, or both. Most thymic carcinomas present at an advanced stage and have a high frequency of relapse, even after complete resection, which indicates the need for a multidisciplinary therapeutic approach (5). Multidisciplinary therapy, including re-excision, radiotherapy and chemotherapy, is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the prognosis was more optimistic in MG without thymoma, both the clinical symptoms of MG and thymoma can be alleviated after thymectomy (Yu et al 2012). However, postoperative recurrence or metastasis is still inevitable and not uncommon (Hishida et al 2016), and few therapeutic options are available for effective treatment of relapsed or refractory thymoma (Simonelli et al 2015). Despite the recommendations for further resection, vast majority of patients will relapse again (Bott et al 2011).…”
Section: Introductionmentioning
confidence: 99%